The cardiovascular safety aspects of calcium supplementations: where does the truth lie? A personal perspective. (February 2015) - Pines, A.; Langer, R. D.
Abstract Clinical guidelines may change with time, as more information from topline studies emerges. Calcium plus vitamin D supplementation became routine decades ago, especially in the older population, based on the assumption that it may promote bone health and prevent fractures, and perhaps induce additional favorable health outcomes. During the past years, an ongoing debate defies this paradigm, mainly because of a potential cardiovascular risk on the one hand, and uncertainty in regard to the extent of the beneficial bone effects on the other hand. The following article summarizes the main recent developments, trying to put some order into the controversial information and opinions which have been published in the medical literature. We conclude that the best current evidence supports a primary strategy of obtaining recommended intakes of calcium and vitamin D from dietary sources. But, since most western diets are inadequate in that regard, and since there is no clear evidence of harm from modest supplementation (up to 1000 mg of elemental calcium and 400 IU of vitamin D3), supplementation is appropriate when dietary intake is inadequate.